2002
DOI: 10.1021/ie0201056
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Fermentation Inhibitors Formed during Pretreatment of Biomass by Polymeric Adsorbents

Abstract: The production of aldehydes that are microbial inhibitors may occur when hexoses and pentoses in an aqueous solution are exposed to temperatures above 150 °C under acidic conditions common to acid-catalyzed lignocellulose biomass pretreatment. Concentrations greater than 0.1% of the degradation product, furfural, strongly inhibit fermentation, as was confirmed for hydrolysate that contained 0.5% (w/o) furfural. Methods of furfural removal that have been reported include sulfite or alkali addition to achieve ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
115
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(122 citation statements)
references
References 23 publications
5
115
1
1
Order By: Relevance
“…For example, polymeric adsorbent XAD-4 was used to adsorb furfural from acid-catalyzed biomass hydrolysate before ethanol fermentation for removal of inhibitory contaminant [147]. This study indicated that such polymeric adsorbents are a very good source of detoxification of the biomass hydrolysate before anaerobic fermentation.…”
Section: Separation Using Ion Exchange Resinsmentioning
confidence: 98%
“…For example, polymeric adsorbent XAD-4 was used to adsorb furfural from acid-catalyzed biomass hydrolysate before ethanol fermentation for removal of inhibitory contaminant [147]. This study indicated that such polymeric adsorbents are a very good source of detoxification of the biomass hydrolysate before anaerobic fermentation.…”
Section: Separation Using Ion Exchange Resinsmentioning
confidence: 98%
“…all produce cocktails of inhibitory chemicals that act to suppress the activities of yeast (and bacteria) in converting hydrolysate sugars to ethanol. Various approaches have therefore been adopted to alleviate the deleterious effects of these inhibitors 98,[126][127][128]136 For example, these can be reduced using steam stripping, nanofiltration membranes, supercritical fluid extraction, or polymeric adsorbent materials (e.g., amberlite resins).…”
Section: Lignocellulosic Hydrolysate Fermentationsmentioning
confidence: 99%
“…The conversion of glucose to ethanol during fermentation of the enzymatic hydrolyzate is not difficult provided there is an absence of inhibitory substances such as furfural, hydroxyl methyl furfural, or natural wood-derived inhibitors such as resin acids (Weil et al 2002). While there are no known natural organisms able to ferment five-carbon (C5) sugars, new yeast strains are being developed that may be able to process both C6 and C5 sugars at high yields (Ragauskas et al 2006).…”
Section: Technical Challenges With Bioconversionmentioning
confidence: 99%